Brown spiders (Loxosceles) are taking hold in Pernambuco, Brazil: a case series, 2018-2022 - Maria Lucineide Porto Amorim; Diógenes Gayo de Oliveira Simão; João Paulo Vieira e Silva de Albuquerque; Beatriz Maria Tenório Ramos; Gustavo José Lopes do Nascimento; Maria Júlia Gonçalves de Mello (Ministério da Saúde do Brasil, 2024)
ABSTRACT Objective To describe accidents involving brown spider (genus Loxosceles) bites notified by the Pernambuco Poison Information and Care Center (CIATox-PE), Brazil, from January 2018 to December 2022. Methods This was a case series study of brown spider bites notified by the CIATox-PE. Results The study included 22 cases with median age of 35 years, the majority being female (13); the cases occurred in rural and urban areas (12 versus 10), at night (10); Petrolina was the municipality with the highest number of notifications (6); spider bites occurred mainly in the lower (11) and upper (9) limbs, almost exclusively inside households (21); specific serum therapy was not indicated for 8 cases because the time for its effectiveness had already elapsed. Conclusion Loxoscelism cases occurred more frequently in females, in both rural and urban areas and mainly at home, with delays in seeking medical care.